Robotic Pill for Biomarker and Fluid Sampling in the Gastrointestinal Tract. (7th April 2022) - Soto, Fernando; Purcell, Emma; Ozen, Mehmet Ozgun; Sinawang, Prima Dewi; Wang, Jie; Akin, Demir; Demirci, Utkan
Abstract : Developing on‐site biomarker enrichment platforms could help to improve the diagnosis of gastrointestinal (GI) tract diseases at early stages. Medical procedures, such as colonoscopies and imaging techniques, are used to diagnose a disease, but are not easily accessible for repeat measurements. In contrast, liquid biopsies, e.g., blood, urine, or fecal samples, have become important sampling strategies to identify health concerns. Herein, a robotic pill is designed for collecting relevant biomarkers from the GI tract over prolonged sampling periods. The robotic pill is comprised of a magnetic core for locomotion, a delayed gate mechanism that controls sampling location based on changes in its environment, and an enrichment module that traps biomarkers in an absorbent matrix while enabling biofluid to pass through the chamber. The robotic pill was assessed to sample microparticles, proteins, and bacteria from the solution. Moreover, the robotic pill was capable of directed locomotion in complex environments and docking in a targeted region against fluid flow. The utilization of an untethered robotic sampling system could provide a tool to investigate aspects of disease initiation and progression for early diagnosis and therapy monitoring. A preprint version of the article can be found at: https://www.authorea.com/doi/full/10.22541/au.164458092.26571169 . Abstract : Screening for cancer at early stages could improve disease prognosis and quality of life. Nevertheless, screening remains challenging for gastrointestinal (GI) cancers due to the limited accessibility. A robotic pill capable of sampling biomarkers (e.g., proteins and bacteria) from liquid samples and robust robotic control, including guidance through predetermined routes and docking against fluid flow is simulated.